Thromboelastography and its use in cardiac surgery - (:unkn) unknown (TURKISH SOC CARDIOLOGY, 2008)
Thromboelastography is an alternative method to conventional coagulation tests for the general evaluation of hemostatic system. Cardiac surgery with cardiopulmonary bypass is accomplished by complex alterations of hemostasis, including acquired dysfunction of platelets, consumption coagulopathy and increased fibrinolysis. Despite major advances in blood conservation methods and perioperative care of the patients, transfusion rates in cardiac surgery remain high. Thromboelastography has an ability to assess almost all components of haemostatic system globally. Currently, thromboelastography is used with standard coagulation tests to decrease the microvascular bleeding and homologous blood transfusion in cardiac surgery with cardiopulmonary bypass. In this review, we aimed to discuss thromboelastography technology and its usage in cardiac surgery.
Keywords: thromboelastography; haemostatic system and cardiac surgery; ARTERY-BYPASS-SURGERY; CARDIOPULMONARY BYPASS; BLOOD-LOSS; ASPIRIN RESISTANCE; MODIFIED THROMBELASTOGRAPHY; EXTRACORPOREAL-CIRCULATION; PLATELET DYSFUNCTION; TRANSFUSION PRACTICE; SURGICAL PATIENTS; TISSUE FACTOR